A specific new biomarker for atrial fibrillation and its sequelae?. (18th November 2022) - Sinner, Moritz F; von Falkenhausen, Aenne S
Graphical Abstract: Graphical Abstract Atrial cardiomyopathy continuously develops over the life span. A healthy (left) and a severely altered (right) atrium are symbolized by electro-anatomical mapping results and by the electrocardiogram rhythm strips in sinus rhythm and atrial fibrillation, respectively. In relation to the progressing atrial cardiomyopathy, bone morphogenetic protein 10 (BMP10) levels, the prevalence of atrial fibrillation, and the risk of stroke also increase. Yet, the exact magnitude and timing of their associations have not been fully determined, as indicated by the increasing degree of uncertainty visualized by the error bars. Electro-anatomical mapping images obtained from the authors' own repositories, with permissions.